Income Shares and Capital Formation: Patterns of Recent Developments - Hein, Eckhard; Kramer, Hagen (Journal of Income Distribution®, 1998)
The development of the functional income distribution in the advanced capitalist economies of France, Germany, the United Kingdom and the U.S.A. has shown a marked shift towards the profit share during the 1980s. Starting from this observation the impact of changing income shares on capital formation is studied in a post-Keynesian framework. Following a model proposed by Bhaduri/Marglin, different patterns of income distribution and capital accumulation are distinguished theoretically and are examined empirically for the manufacturing sectors of the investigated economies. It is concluded that the development of the profit share and the rate of capital accumulation on average over the business cycle implies that the conditions for the co-operative “wage-led growth” have been established again during the cycle covering the 1980s, although these opportunities for co-operation have not been realized by the supply-side politics.